(untitled) (PJDOL, 2023)
Clicking, posting and scrolling are not the only purpose of social media. Social media has become multipurpose forum for the people. In the educational sector, the use of social media as interactive tools which motivate students towards learning. The aim of this research is to investigate the impact of social media on students’ learning in Iqra University, Karachi. Researchers conducted a complete review of the impact of social media for university students’ learning, identified the significant factors and deliberated on new models which were based on different research studies. By using random sampling technique, students were selected for data collection.